The Michigan Plan for Appropriate Tailored Healthcare in Pregnancy Prenatal Care Recommendations. Issue 4 (October 2021) - Peahl, Alex Friedman; Zahn, Christopher M.; Turrentine, Mark; Barfield, Wanda; Blackwell, Sean D.; Roberts, Suni Jo; Powell, Allison R.; Chopra, Vineet; Bernstein, Steven J.
Abstract : OBJECTIVE: To describe MiPATH (the Michigan Plan for Appropriate Tailored Healthcare in pregnancy) panel process and key recommendations for prenatal care delivery. METHODS: We conducted an appropriateness study using the RAND Corporation and University of California Los Angeles Appropriateness Method, a modified e-Delphi process, to develop MiPATH recommendations using sequential steps: 1) definition and scope of key terms, 2) literature review and data synthesis, 3) case scenario development, 4) panel selection and scenario revisions, and 5) two rounds of panel appropriateness ratings with deliberation. Recommendations were developed for average-risk pregnant individuals (eg, individuals not requiring care by maternal–fetal medicine specialists). Because prenatal services (eg, laboratory tests, vaccinations) have robust evidence, panelists considered only how services are delivered (eg, visit frequency, telemedicine). RESULTS: The appropriateness of key aspects of prenatal care delivery across individuals with and without common medical and pregnancy complications, as well as social and structural determinants of health, was determined by the panel. Panelists agreed that a risk assessment for medical, social, and structural determinants of health should be completed as soon as individuals present for care. Additionally, the panel provided recommendations for: 1) prenatal visit schedules (care initiation, visit timing and frequency, routine pregnancy assessments), 2) integration of telemedicine (virtual visits and home devices), and 3) care individualization. Panelists recognized significant gaps in existing evidence and the need for policy changes to support equitable care with changing practices. CONCLUSION: The MiPATH recommendations offer more flexible prenatal care delivery for average-risk individuals. Abstract : The RAND Corporation and University of California Los Angeles Appropriateness Method was used to develop new average-risk prenatal care delivery recommendations pertaining to visit frequency, telemedicine, and social and structural determinants of health.